Synergy between the National Narcotics Agency and the Police in Handling Narcotics Crimes in Indonesia - Ahmad Baqi; Wahdaniah Sitorus; Syifatul Zuhra; Regita Angraini Lubis (Jurnal Sahabat ISNU SU, 2025)
Drug abuse and illicit trafficking are serious problems in the Indonesian criminal justice system that require comprehensive and equitable handling. Law Number 35 of 2009 concerning Narcotics regulates a dual approach through repressive law enforcement against dealers and a rehabilitative approach for drug abusers. However, in practice, the implementation of rehabilitation is still not optimal and tends to be replaced by imprisonment. This study aims to analyze the law enforcement policy for narcotics crimes in Indonesia, focusing on the role of the National Narcotics Agency and the Police and the implementation of rehabilitation for drug abusers. The research method used is normative legal research with a legislative and conceptual approach. The results show that there is still a gap between legal norms and law enforcement practices, particularly in the implementation of rehabilitation, and the need to strengthen synergy between the National Narcotics Agency and the Police. This study concludes that optimizing rehabilitation policies and institutional coordination are key to realizing just, humanistic, and social recovery-oriented narcotics law enforcement.